2018
DOI: 10.12788/jhm.2911
|View full text |Cite
|
Sign up to set email alerts
|

How Does Your PICCOMPARE? A Pilot Randomized Controlled Trial Comparing Various PICC Materials in Pediatrics

Abstract: BioFlo® PICCs appear potentially safer for pediatrics than traditional standard care PICCs with a clamp. Further research is required to definitively identify clinical, cost-effective methods to prevent PICC failure and improve reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 30 publications
0
42
0
Order By: Relevance
“…Miyagaki et al's (2012) findings were not included in this meta-analysis as no thromboses were detected in this study. Overall, meta-analysis (including Kleidon et al, 2018) showed no significant difference in thrombosis between experimental and control arms (RR 0.98, 95% CI 0.87, 1.11), with low heterogeneity (I 2 = 0%; Figure 1). Sub-group analysis of thrombosis rates in studies assessing pediatric and adult populations was conducted.…”
Section: Primary Outcomementioning
confidence: 97%
“…Miyagaki et al's (2012) findings were not included in this meta-analysis as no thromboses were detected in this study. Overall, meta-analysis (including Kleidon et al, 2018) showed no significant difference in thrombosis between experimental and control arms (RR 0.98, 95% CI 0.87, 1.11), with low heterogeneity (I 2 = 0%; Figure 1). Sub-group analysis of thrombosis rates in studies assessing pediatric and adult populations was conducted.…”
Section: Primary Outcomementioning
confidence: 97%
“…This pilot RCT compared a hydrophobic polyurethane PICC with proximal valve with a power-injectable polyurethane PICC with external clamp to reduce PICC failure and complications in an adult population. This study followed the same methodology as the paediatric protocol [35] and published study [26] and was reported in line with the CONSORT guidelines. A quarter of PICCs failed (25/110; 23%) before treatment completion.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pilot RCT in paediatric patients [26] compared a polyurethane, power-injected PICC with an external clamp to a hydrophobic polyurethane PICC (BioFlo®). Failure was halved in the hydrophobic polyurethane group (8/72; 11%) compared to standard care (16/74; 22%) (p = 0.087), which when expressed as an incident rate was 12.6 and 7.3 per 1000 PICC days (incident rate ratio 0.58; 95% confidence interval (CI) 0.21-1.43; p = 0.172).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when PICCs are trimmed to a more suitable length for pediatric patients (Interface Biologics 2017), the risk of thrombotic complications including occlusion is greatly reduced. A recent randomized control trial in pediatric inpatients demonstrated a 50% reduction in PICC failure when antithrombogenic catheters were used compared to a power injectable polyurethane PICC (Kleidon et al 2018). Additionally, significantly fewer complications such as occlusion occurred in patients with antithrombogenic PICCs.…”
Section: Catheter Materials and Designmentioning
confidence: 99%